The Effect of Innovation Diffusion Communication on Community Participation in the Kampung Zakat Program, Bunga Raya District, Siak Regency - Nureta Dwika Handayani; Anggra Agastyassa Owie; Nurfauzy Lubis (Universitas Nurul Jadid, 2023)
Low public awareness of the obligation to tithe is one of the motivations and ideas in the emergence of the Kampung Zakat Program. The efforts to develop the Kampung Zakat Program carried out by the government and the people of Bunga Raya District cannot be separated from the participation and active involvement of community members. The main capital in the implementation of the Zakat Village Program is the expertise of the facilitator or amil zakat in communicating and innovating, so as to generate community participation in development and want to participate in activities as well as take part in zakat. The aim of this study was to find out and analyze how much influence innovation diffusion communication has on community participation in the Kampung Zakat Program, Bunga Raya Village, Siak Regency. This research use quantitative research with assosiative design. Data collection techniques by observation, interviews, distributing questionnaires and documentation. Sampling used the slovin technique and a total sample of 98 people was obtained from 4433 total populations from UPZ members of Bunga Raya District and the community involved in the Zakat Village Program. The results showed that from the hypothesis test there was a significant influence between the X and Y variables with a significant value of 0.000 <0.05, and a T valuecount>Ttable (30,677 > 1,985) and the percentage contribution of the variable effect is 90.7%.